2018
DOI: 10.15761/tim.1000163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological characteristics of ocular surface squamous neoplasia: Evidence from a tertiary eye care center, northwest Ethiopia

Abstract: Background: Ocular surface squamous neoplasia is a spectrum of diseases encompassing from mild dysplasia to invasive squamous cell carcinoma of the ocular surface.Patients and methods: A series of 50 cases with suspected ocular surface squamous neoplasia presenting to Gondar University Hospital Tertiary Eye Care and Training Center, Northwest Ethiopia from January 2015 to June 2016 were enrolled. Clinical parameters were documented through interviewer administered questionnaire and ocular examination. Excision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…The peak age group of patients affected by OSSN was 30-39 years, slightly younger than the general average age of OSSN that have been reported in Nigeria and across sub-Saharan Africa which is usually in the 40-49 years age group. [13][14][15] However, in keeping with previous reports, the condition occurs in a much younger age group in our patients as compared to studies in Caucasian populations and this has been attributed to the higher association of OSSN cases in the tropics with HIV/AIDS. [2,3,16,17] This study reveals a predominant affectation of males in disagreement with early observations across sub-Saharan Africa where an equal sex prevalence was generally reported.…”
Section: Association Of Ossn With Hiv Infectionsupporting
confidence: 89%
See 2 more Smart Citations
“…The peak age group of patients affected by OSSN was 30-39 years, slightly younger than the general average age of OSSN that have been reported in Nigeria and across sub-Saharan Africa which is usually in the 40-49 years age group. [13][14][15] However, in keeping with previous reports, the condition occurs in a much younger age group in our patients as compared to studies in Caucasian populations and this has been attributed to the higher association of OSSN cases in the tropics with HIV/AIDS. [2,3,16,17] This study reveals a predominant affectation of males in disagreement with early observations across sub-Saharan Africa where an equal sex prevalence was generally reported.…”
Section: Association Of Ossn With Hiv Infectionsupporting
confidence: 89%
“…[3,18,19] However, some recent studies have revealed a male predominance for OSSN in sub-Saharan Africa. [13,14] These variations in sex prevalence are probably related to differences in study design as most of the single institution-based studies show a male predominance whereas the larger scale studies show an equal sex distribution. A female predominance has also been reported in occasional studies, [20] again highlighting the selection bias inherent in single institution-based studies.…”
Section: Association Of Ossn With Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation